Does firm performance reveal its own causes? the role of Bayesian inference - Tang, Ying‐Chan; Liou, Fen‐May (Strategic Management Journal, 2009)
Abstract A central problem in strategic management is how the inference ‘sustainable competitive advantage generates sustainable superior performance’ can be put into practice. In this article we develop a theoretical framework to understand the causal relationships among (1) sustainable competitive advantage, (2) configuration, (3) dynamic capability, and (4) sustainable superior performance. We propose that a firm's competitive advantage, resource bundle configuration, and dynamic learning capability cannot be comprehended by outsiders. Its operational performance, however, can be captured by financial indicators. We promote an inductive Bayesian interpretation of the sustainable competitive advantage proposition. From this viewpoint, the presence or absence of competitive advantage may be reflected in the causal relationship between resource configuration, dynamic capability, and observable financial performance. We apply this theoretical framework to an example drawn from the global semiconductor industry, an area in which resource configuration and dynamic capability are essential to performance. The paper concludes with a summary of the proposed model and suggestions for future theoretical development of strategic management. Copyright © 2009 John Wiley & Sons, Ltd.